Impact of quantitative easing and tax policy on income inequality: Evidence from Japan - Naoyuki Yoshino; Farhad Taghizadeh-Hesary; Sayoko Shimizu (Asian Development Bank Institute (ADBI), 2018)
From April 2013 until May 2016, Japan's monetary base rose from ¥155 trillion to ¥387 trillion as part of the Bank of Japan's (BOJ) quantitative and qualitative easing (QQE) monetary policy for achieving a price stability target of 2%. Although the main objective of the BOJ's quantitative easing (QE) and QQE policy is inflation targeting, this paper aims to shed light on the impact of the policy on income inequality. At the same time, this paper assesses the impact of Japanese tax policy on income inequality through the development of a vector error correction model for the period Q1 2002-Q4 2016 by including the five variables of income inequality, money stock, government income tax, the stock price index, and real gross domestic product. The empirical results reveal that the QE and QQE monetary policy of the Bank of Japan increased income inequality through a rise in the price of financial assets that benefited only richer income groups and resulted in a widening of the income gaps between different income groups. On the other hand, tax policy mitigated part of the adverse effect. The results indicate that monetary policy has both a short-run impact and long-run impact on income inequality, while tax policy has only long-run impact.
Keywords: D63; E52; H24; 330; income inequality; quantitative easing; monetary policy; tax policy; Japanese economy